2017
DOI: 10.3945/jn.116.239574
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effects of Plant Compared with Animal Protein Sources on Features of Metabolic Syndrome

Abstract: Dietary protein may play an important role in the prevention of metabolic dysfunctions. However, the way in which the protein source affects these dysfunctions has not been clearly established. The aim of the current systematic review was to compare the impact of plant- and animal-sourced dietary proteins on several features of metabolic syndrome in humans. The PubMed database was searched for both chronic and acute interventional studies, as well as observational studies, in healthy humans or those with metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 149 publications
4
85
3
Order By: Relevance
“…These results are contradictory to a metaanalysis that showed statistically beneficial relationships between soy protein intake with hypertension, lowering serum cholesterol and glucose levels. 34 Despite the beneficial metabolic effects observed in this study, a relationship between soy protein consumption and MetS risk factors could not statistically be confirmed.…”
Section: Discussioncontrasting
confidence: 65%
“…These results are contradictory to a metaanalysis that showed statistically beneficial relationships between soy protein intake with hypertension, lowering serum cholesterol and glucose levels. 34 Despite the beneficial metabolic effects observed in this study, a relationship between soy protein consumption and MetS risk factors could not statistically be confirmed.…”
Section: Discussioncontrasting
confidence: 65%
“…(41) In another recent systematic review of studies comparing plant with animal protein intake in relation to metabolic syndrome-related conditions, authors concluded that soy protein (with isoflavones), but not soy protein alone or other plant proteins, led to greater decreases in total and LDL cholesterol compared with animal-sourced protein intake. (60) Future research should investigate the long-term of effects on changes in cardiometabolic health of specific food sources of protein, other components (e.g., food matrices) of plant versus animal protein sources and/or differences in diet quality between those consuming more protein from plants or animals, and vice versa. For example, one question might be whether low saturated fat or high fiber protein food sources have a different relationship with cardiometabolic health than high saturated fat or low fiber protein sources.…”
Section: Discussionmentioning
confidence: 99%
“…Higher protein intake, particularly from plant-based sources, may also be associated with attenuated inflammatory burden in aging populations [16]. In diabetics, replacing animal protein with plant proteins may help to improve glycaemic control and prevent the onset of risk factors associated with CVD [14,17,18].…”
Section: Introductionmentioning
confidence: 99%